ETHNOLINGUISTIC CHARACTERISTICS OF CLOTHING NAMES IN ENGLISH AND UZBEK LANGUAGES - Normurodova Farogat Tojimurod kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the ethnolinguistic characteristics of clothing names in English and Uzbek. Clothing terminology is analyzed as a culturally marked lexical field reflecting national identity, social structure, religious values, environmental conditions, and historical development. Through comparative semantic and linguocultural analysis, the study identifies similarities and differences in how clothing names encode ethnocultural information in both languages. The findings show that Uzbek clothing terminology demonstrates a high degree of national-cultural markedness, while English clothing lexicon reflects institutional, functional, and socio-historical factors shaped by modernization and globalization.